2015
DOI: 10.1007/s00198-015-3293-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social isolation on delayed hospital discharges of older hip fracture patients and associated costs

Abstract: High risk of social isolation, social isolation and referral to public-funded rehabilitation units increase delays in patients' discharges from acute care hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 27 publications
5
61
3
Order By: Relevance
“…Patients living independently may live as much or even more in social isolation as patients in nursing homes do. In the literature there is some evidence that the presence of family members in the hospital will help to reduce the incidence of delirium [30], moreover, that social isolation leads to a prolonged hospitalization [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Patients living independently may live as much or even more in social isolation as patients in nursing homes do. In the literature there is some evidence that the presence of family members in the hospital will help to reduce the incidence of delirium [30], moreover, that social isolation leads to a prolonged hospitalization [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Patients with ALC are commonly characterized by cognitive impairment [4, 610] including dementia [6, 11], behavioral challenges [12], functional decline [4, 79], social vulnerability [13, 14] and advanced age [15–17]. Contextual risk factors for ALC include lack of community services [8, 18] or LTC beds [11, 1921], lack of timely coordinated care, lack of presence or willingness of family carers [4, 22] and hospital discharge policies which influence length of stay and discharge planning capacity.…”
Section: Introductionmentioning
confidence: 99%
“…9 Cognitive decline, depression, and functional limitations have each been associated with social isolation. [10][11][12][13] Socially isolated older adults may encounter more challenges at the end of life (EOL) due to the absence of an appropriate healthcare agent. Prior studies have suggested that social isolation hinders ACP.…”
mentioning
confidence: 99%